A note on lower pressure and higher pressure metamorphic belts in North Portugal - I. S. Oen (Netherlands Journal of Geosciences, 1974)
In north portugal a lower pressure metamorphism occuring in belts associated with Older Hercynian Granites includes low and intermediate pressure facies types. A higher pressure metamorphism occurring in belts outside the main granite area includes intermediate to high pressure facies types.